The Anti-Inflammatory Effect of Omega-7 Against Cisplatin in Rat Model - Mahmood, Shrouq H; Hassan, Ali F (The Iraqi Journal of Veterinary Medicine, 2022)
Omega-7 (palmitoleic acid, 16:1 n7) is a monounsaturated fatty acid that is found to have several beneficial effects. Cisplatin is commonly considered for the treatment of different carcinomas. Cisplatin therapy is restricted due to its nephrotoxicity. Nephrotoxicity caused by cisplatin is thought to be associated with inflammatory reactions among other mechanisms. The aim of the present study was to evaluate the possible anti-inflammatory effect of omega-7 on cisplatin in rats. Thirty adult male Wistar Albino rats were divided randomly into five equal groups, rats of group 1 received liquid paraffin solution orally for 7 consecutive days, rats of group 2 received cisplatin (7.5 mg/kg) by single intraperitoneal injection, rats of group 3 received omega-7 (50 mg/kg) by oral administration for 7 days consecutively and then followed by single cisplatin (7.5 mg/kg) intraperitoneal injection on the eighth day, rats of group 4 received omega-7 (100 mg/kg) by oral administration for 7 days consecutively followed by single intraperitoneal injection of cisplatin (7.5 mg/kg) on the eighth day, rats of group 5 received omega-7 only (100 mg/kg) orally for 7 consecutive days. On day 9, all animals were euthanized and then serum samples were utilized for assessment of tumor necrosis factor-alpha (TNF-α), interleukin-10 (IL-10) and interleukin-1β (IL-1β). Treatment of rats with omega-7 had led to significant decline in the activities of the pro-inflammatory cytokines TNF-α and IL-1β, and significant reduction in the level of IL-10. Omega-7 has an anti-inflammatory effect against cisplatin adverse effects.